The Effects of Online Learning on Students' Scientific Argumentation Ability on Thermodynamic Topics - Dewi Priyantini; Supriyono Koes-H; Eny Latifah (Jurnal Pendidikan Sains, 2021)
Abstract:. Scientific argumentation is a cognitive complex that requires scientific reasoning related to theory and evidence of critical thinking related to the argument. The purpose of this study is to analyze the ability of scientific argumentation on the topic of Thermodynamics in online learning. The sample in this study were 100 students of class XII at SMA Negeri 1 Pacitan who had studied Thermodynamics through face-to-face learning and online learning. Data on scientific argumentation skills were obtained through 11 two-tier questions accompanied by student explanations and arguments, reliability coefficient 0.715 with criteria high. The assessment is based on the TAP rubric which consists of 5 aspects including claims, data, warrant, qualifier, and rebuttal. The results of the analysis show that the students' arguments are still low on the aspects of warranting and backing. students provide reasons not accompanied by proof of the concept of thermodynamics, but students only give opinions that they think are correct and based on the knowledge they have experienced and observed.Abstrak: Argumentasi ilmiah adalah keterampilan kognitif kompleks yang membutuhkan penalaran ilmiah terkait korelasi teori dan bukti serta pemikiran kritis terkait dengan kekuatan argumen. Penelitian ini bertujuan menganalisis kemampuan argumentasi ilmiah pada topik Termodinamika pada pembelajaran daring. Sampel yang digunakan dalam penelitian ini sebanyak 100 siswa kelas XII di SMA Negeri 1 Pacitan yang telah memperoleh materi topik Termodinamika melalui pembelajaran tatap muka dan pembelajaran online. Data keterampilan argumentasi ilmiah diperoleh melalui pemberian 11 soal berupa tes pilihan disertai dengan penjelasan dan argumentasi siswa, dengan reliabilitas 0,715. Penilaian dilakukan berdasarkan rubrik TAP yang terdiri dari 5 aspek yaitu klaim, data, warant, qualifer dan rebuttal. Hasil analisis menunjukkan argumentasi siswa masih rendah pada aspek pemberian warrant dan backing. Pemberian alasan tidak disertai dengan bukti konsep Termodinamika melainkan siswa hanya memberikan pendapat yang menurut mereka benar dan berdasarkan pengetahuan yang mereka telah alami dan amati.